Potensi Ekstrak Bawang Hitam sebagai Tabir Surya terhadap Paparan Sinar Ultraviolet - Putu Srinata Dampati (Direktorat Penerbitan dan Publikasi Ilmiah Universitas Surabaya, 2020)
Abstract—Skin cancer is in the third rank in Indonesia. One of the causes of skin cancer is excessive exposure to ultraviolet rays from the sun. Ultraviolet radiation forms Reactive Oxygen Species that disrupts the regulation of the cell-matrix and causes photoaging and the burden of gene mutations that cause carcinogenesis. Black garlic is fermented garlic with a certain duration, temperature, and humidity. Black garlic has higher levels of antioxidants than garlic. Aimsresearch to determine the potential of black garlic extract as a sunscreen against ultraviolet rays. Literature study using literature review articles and research articles from international and national journals within the last ten years. Result research show black garlic extract protects the skin from ultraviolet radiation, acts as a photoprotector, prevents photoaging by stimulating fibroblast orders and prevents collagen I degradation, and prevents carcinogenesis. Black Garlic extract has a potency become sunscreen against ultraviolet exposure due to its antioxidant content. Further research is needed on the dosage and side effects. Keywords: antioxidants, black garlic, reactive oxgyen species, ultraviolet